IMPLEMENTASI METODE SAW UNTUK REKOMENDASI MENU TERLARIS DI COFFEE SHOP - Sirait, Anisa; Sulistyohati, Aprilia; Susanto, Arif (Fakultas Teknik dan Informatika, Universitas Dian Nusantara, 2024)
In the era of rapid globalization, technological developments and changes in people's lifestyles affect various aspects of life, including the coffee shop business which is experiencing significant growth. Lanaka coffee shop, which focuses on coffee drinks and snacks, faces challenges in recommending best-selling menus due to rapidly changing customer tastes and market trends. To overcome this problem, this research proposes the use of the Simple Additive Weighting (SAW) method as a solution to recommend the best-selling menu at Coffee Shop Lanaka. The SAW method was chosen due to its ability to accurately assess menu criteria by considering predetermined weights. The process involves setting criteria that include taste, price, portion, and number purchased, and assigning fuzzy weights to each criterion. The weighting system is performed dynamically based on sales data and customer feedback, with two types of criteria: benefit and cost. The calculation results from the SAW method are used to rank the menu alternatives and provide the most suitable recommendation. With this approach, it is expected to increase customer satisfaction and profitability of Coffee Shop Lanaka through more efficient and up-to-date data-driven menu management